My Mother: An Unwritten Environmental Education Curriculum - Sitthiraksa, Sinith (UnderCurrents: Journal of Critical Environmental Studies, 1993)
One day last winter, my classmates and I had a deep and broad discussion on the topic of environmental education curriculum.1 As the only student from Thailand in the class, I was surprised to see that many of the colourful curriculum guidebooks provided for Canadian students were designed to teach the children here how to touch, to hug and to kiss the trees. [...]